Assessment of Simplifications to a Pseudo–2D Electrochemical Model of Li-ion Batteries. Issue 1 (2019) - Kong, XiangRong; Wetton, Brian; Gopaluni, Bhushan
Abstract: Lithium-ion batteries are ubiquitous in modern society. Their high power and energy density compared to other forms of electrochemical energy storage make them very popular in a wide range of applications [1]. To ensure safe, prolonged, and reliable operations, significant research effort has been put into understanding, modelling, and predicting the key limiting phenomena, which has led to various battery models with different levels of complexity and prediction capabilities [2]. This work focuses on implementing the pseudo-two-dimensional (P2D) model, the most widely accepted electrochemical model on lithium-ion batteries. The unparalleled prediction abilities of the P2D model, however, are over shadowed by its high complexity. Thus, much of this work focuses on model reduction to shorten effective simulation time. In the end, four model reductions have been identified and successfully implemented. Comparisons to the full model at 1C, 2C and 5C discharge rates are reported.